The Future of China and the Chinese Language in Global Higher Education - Altbach, Philip (International Higher Education, 2022)
There has been much debate about the emergence of Chinese universities on the world stage and the potential role of the Chinese language as a global scientific medium. I argue that while China’s top universities have done well in rankings, there are structural and other impediments to their taking global leadership. Further, English is sufficiently dominant as the global medium of science that Chinese has no possibility of serving as a key global academic language.